"Toen Johannes in de gevangenis niet over het optreden van de Messias hoorde" (Matt. 11:2): De wederwaardigheden van een opmerkelijke conjectuur (cj16154) en zijn bedenker - Zwiep, Arie W. (Kerk en theologie, 2023)
This article examines a conjectural emendation proposed by David Friedrich Strauss (1808-1874) in the Greek text of Matthew 11:2 (about John the Baptist). Strauss expressed surprise that his opponents, both orthodox and rationalist scholars, had not themselves suggested this correction. Although Strauss ultimately did not endorse the conjecture, his treatment of the subject in the different editions and translations of Das Leben Jesu kritisch bearbeitet (1835-1840) sheds light on his interactions with his opponents and provides insight into the dynamics of a controversy during the early stages of critical research on the Life of Jesus.